Inventarisasi Jenis Burung di Kawasan Cikaniki, Taman Nasional Gunung Halimun Salak - Nasywa, Fatihah; Rose, Arine Ellen; Adinda, Ratu Celina; Talia, Sarah; Azmi, Aulia; Sari, Yusiana Fatika; Hidayah, Rizka Rifaatul; Aryanto, Glorio Brian; Syani, Mutiara; Isfaeni, Hanum; Komala, Ratna (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
Indonesia possesses extraordinarily high biodiversity, including numerous bird species inhabiting tropical rainforests. This study aimed to inventory and characterize birds in Citalahab Village, Gunung Halimun Salak National Park, one of Indonesia's largest tropical rainforest areas. Surveys were conducted on May 2 and 3, 2024, using transect methods. The research identified 70 bird species from 6 orders, with Passeriformes being the most abundant. The relative abundance index highlighted the dominant presence of the Collocalia linchi in the region. Environmental factors such as vegetation type and temperature significantly influenced bird distribution and diversity. The findings underscore the critical role of forest habitat conservation in preserving bird species diversity. This research contributes valuable insights into the understanding of bird diversity in Indonesian tropical rainforests and advocates for further conservation efforts.